Innovative Community Service Programs with Local Participation to Build Independent Villages - Abidin, Zaenal (Zabags International Journal of Engagement, 2024)
This study investigates the innovations in a community service program that is based on local participation in East Tanjung Jabung, Jambi Province, Indonesia, and its effects on the growth of independent communities. The study included a variety of stakeholders, including village chiefs, locals, university community service teams, and non-governmental organizations. It used a qualitative approach and case study design. The findings demonstrated how community involvement in the design, execution, and assessment of programs improved their efficacy and long-term viability. There were notable social and economic benefits, such as higher income and more work options, from initiatives like non-formal education and entrepreneurship training. To increase the program's future performance, the report suggests creating management groups, bolstering evaluation procedures, and collaborating with the commercial sector. The local participation-based strategy has a lot of promise for developing independent villages that are secure and long-lasting